The Effect Of Workforce Transformation And Human Resource Development On The Performance Of Msmes Fostered By Palu City Business Incubator - Adelia Maharani; Risnawati Risnawati; Bakri Hasanuddin; Priclya Chintya Dewi (UNIVED Press, 2026)
This study aims to analyze the effect of workforce transformation and human resource development on the performance of MSMEs under the guidance of the Palu City Business Incubator. A quantitative approach was used with a descriptive and causal design, involving 50 active MSMEs as samples obtained through purposive sampling. Primary data were collected through a Likert scale-based questionnaire and analyzed using multiple linear regression. The results show that workforce transformation has a positive and significant effect on MSME performance. Human resource development has also been proven to have a significant effect and is the most dominant variable in improving MSME performance. Simultaneously, workforce transformation and human resource development have a significant effect on MSME performance. These findings confirm that strengthening human resource capacity and workforce transformation are crucial strategies for improving the productivity, competitiveness, and sustainability of MSMEs in an increasingly competitive market.